2020
DOI: 10.2139/ssrn.3693374
|View full text |Cite
|
Sign up to set email alerts
|

When Do Firms Highlight Their Effective Tax Rate?

Abstract: Acknowledgements: We thank the participants of the 2013 arqus Doctoral Workshop and participants at the 2018 European Accounting Association conference for their valuable comments on an earlier version of this paper. We are grateful to the Baetge research team for sharing the annual report quality data and thank Fabian Peitz and Isis Swoboda for excellent research assistance. We gratefully acknowledge funding provided by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation)-Project-ID 403041268… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Demeré et al (2019) provide empirical evidence that firms smooth their GAAP ETRs. Consistently, Flagmeier et al (2020) find that firms strategically disclose information on their GAAP ETR more visibly if their ETR is favorable from an investor's perspective (low or close to the average ratio for firms of the same industry or size group). Overall, these findings indicate that firms actively manage investors' perception in their tax disclosure strategy.…”
Section: Management Of Tax Perception and Its Impact On Stakeholdersmentioning
confidence: 70%
“…Demeré et al (2019) provide empirical evidence that firms smooth their GAAP ETRs. Consistently, Flagmeier et al (2020) find that firms strategically disclose information on their GAAP ETR more visibly if their ETR is favorable from an investor's perspective (low or close to the average ratio for firms of the same industry or size group). Overall, these findings indicate that firms actively manage investors' perception in their tax disclosure strategy.…”
Section: Management Of Tax Perception and Its Impact On Stakeholdersmentioning
confidence: 70%
“…The study corroborated the findings of previous studies that the exempt income accretion strategy of the identified banks was used as a qualifying tax shelter by companies. In Flagmeier et al ’s (2020) study on factors guiding disclosure behavior on ETRs by firms, the findings showed that firms tend to highlight ETRs when they are favorable and seldom avoid disclosures when ETR figures go north. Some errors underlie this assumption, considering that ETRs disclosures and their reconciliation to the statutory tax rate in financial statement footnotes is guided by the requirements of International Accounting Standard 12 on income taxes (Section 8, Subsection 1) and ASC 740 for companies reporting under the US GAAP.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Other researchers examined the sources of declining ETRs for select groups of multinational and domestic firms using both cross-sectional and time-trend data on the ETR effects of each element of the reconciliation items (Drake et al , 2017; Flagmeier et al , 2020; McGill and Outslay, 2004; Nwachukwu and Mohammed, 2012). Drake et al (2017) highlighted the frequency, tax rate impact and the magnitude of the absolute dollar benefit of each reconciliation item across the spectrum of the multinational enterprises and domestic firms studied.…”
Section: Literature Reviewmentioning
confidence: 99%